OPTIMALISASI PENGEMBANGAN PRODUK WIRAUSAHA MENJADI PRODUK UNGGULAN DI DESA WISATA TUGU SELATAN, JAWA BARAT - Retno Widowati; Farizal Marzuki; Kania Farida; Saprudin; Edison Parlindungan (POLITEKNIK LP3I JAKARTA, 2025)
To support the development of the economic potential of the Tugu Selatan tourist village, Cisarua, West Java, village business entities and lecturers from six universities collaborated to optimize entrepreneurial products into superior products in the village. This is crucial for improving the quality and competitiveness of MSMEs, which are the backbone of the regional economy, particularly in Kampung Koboi and Kampung Susu. MSMEs play a vital role in the national and regional economy. However, many MSMEs experience difficulties in business and financial management and require a better understanding of aspects of entrepreneurship, business legality, financial management, and more. Therefore, we held a Community Service Program as one of the implementations of the Tri Dharma (Three Pillars of Community Empowerment). This program included training and mentoring for entrepreneurs in the Tugu Selatan tourist village, Cisarua, West Java, specifically Kampung Koboi and Kampung Susu, to help them develop their products into superior products with global competitiveness. The community service activities took the form of training and mentoring. The participants were satisfied with the program and are willing to participate in similar activities and mentoring in the future